Prenatal diagnosis of omphalocele, exstrophy of the cloaca, imperforate anus and anomalies of the spine (OEIS complex) - Torres-Cepeda, Duly (2021)
Omphalocele, cloacal exstrophy, imperforate anus and spinal anomalies complex (OEIS complex) is a combination of severe and extremely rare congenital malformations. Its incidence is estimated at 1 per 200,000 - 400,000 live births. The occurrence of cases is sporadic and has no known etiology. Some have been associated with environmental exposures, genetic causes, and in vitro fertilization procedures. The mechanism of development appears to be associated with alterations in early blastogenesis or defect in mesodermal migration during the embryonic period. Prenatal diagnosis can be made at 16 weeks of gestation, although earlier diagnosis is sometimes possible. Definitive diagnosis is made necropsy findings. Most surviving newborns require multiple surgeries with potential complications and the desired results are not always achieved. A case of prenatal diagnosis of omphalocele, cloacal exstrophy, imperforate anus and spinal anomalies (OEIS complex) is presented.